2019
DOI: 10.1002/open.201800261
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Zinc Ferrites: Safe and Efficient Nanolabels for Cell Imaging and Tracking In Vivo

Abstract: Manganese‐zinc ferrite nanoparticles were synthesized by using a hydrothermal treatment, coated with silica, and then tested as efficient cellular labels for cell tracking, using magnetic resonance imaging (MRI) in vivo. A toxicity study was performed on rat mesenchymal stem cells and C6 glioblastoma cells. Adverse effects on viability and cell proliferation were observed at the highest concentration (0.55 mM) only; cell viability was not compromised at lower concentrations. Nanoparticle internalization was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In addition, a toxicity research work was performed by Herynek et al ., on rat mesenchymal stem cells and C6 glioblastoma cells. [18] They have conducted that the studied cells produced a distinct hypointense signal in T 2 -or T 2 *-weighted MRI in vivo . The results of both mentioned studies and the results of the present work are in a good agreement to confirm the hypothesis of important issues of MZF NPs as an MRI contrast agent for cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a toxicity research work was performed by Herynek et al ., on rat mesenchymal stem cells and C6 glioblastoma cells. [18] They have conducted that the studied cells produced a distinct hypointense signal in T 2 -or T 2 *-weighted MRI in vivo . The results of both mentioned studies and the results of the present work are in a good agreement to confirm the hypothesis of important issues of MZF NPs as an MRI contrast agent for cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…Other thulium-based sensors have also been reported [69]. Finally, manganese-zinc ferrite nanoparticles [70,71] and manganese-porphyrin bimodal agents [72] are among other types of sensors that are also being explored. The interest in non-Gd 3+ -based agents stems from the studies that have reported adverse effects for Gd 3+ -based MRI agents, most notably, nephrogenic systemic fibrosis (NFS) in patients with severe renal insufficiency [73].…”
Section: Malikidogo Et Al Introduced a Different Bimodal Zinc Sensor (Figurementioning
confidence: 99%
“…The increased r 1 value of MZF@TPGS formulation may be due to the protonation and hydration of polymer, thereby resulting in the entry of water molecules into cluster-like area, the interacting with the metal of Mn and Zn, shortening the relaxation time and giving rise to positive or negative contrast on T 1 - or T 2 -weighted magnetic resonance images [ 50 ]. Compared to reported silica-coated MZF core [ 51 ] or worm-like formulated MZF [ 52 ] with higher r 2 value for T 2 -weighted MR contrast, our prepared MZF@TPGS formulation revealed dual MR contrast ability due to the balance in T 1 - or T 2 -weighted imaging.…”
Section: Resultsmentioning
confidence: 71%